Researches of Thai Herbs for Osteoarthritis Treatment - ประดิษฐ์ วารณี; ชมเดช สิริวดี; งานวงศ์พาณิชย์ กรกฎ (KKU Science Journal, 2014)
Osteoarthritis is a chronic joint disease mostly found in elder people and animals. Gradual degradation of articular cartilage is the important symptom causing joint pain. Pathogenesis of this disease is complex and involves with many responsive mechanisms particularly inflammation. This mechanism can induce imbalance of joint homeostasis resulting in over production of enzyme that could digest extracellular matrix components of cartilage. Treatment of osteoarthritis using analgesic drugs including non-steroidal anti-inflammatory drugs (NSAIDs) is only one way to alleviate pain which brings some unwanted side effects. Nowadays, searching of plant extracts which has potential to resist inflammation with chondroprotective properties for osteoarthritis treatment has been increasing continuously. There are some scientific evidences showing the efficiency of some common Thai herbs for anti-arthritis. This article reviewed the efficacy and proposed mechanisms of some Thai herbs including turmeric, ginger, betel and moringa that can relieve osteoarthritis symptoms particularly inflammation and pain management.